Numerical study of extreme waves driven by synthetic tropical cyclones in the northwest Pacific Ocean - Du, Shengtao; Yan, Zhiduo (Frontiers in Environmental Science, 2023)
Extreme waves induced by the extreme tropical cyclone (TC) with very strong intensity threaten marine production and transportation. In this paper, six tropical cyclones with typical track and extreme strong intensity were synthesized to study the extreme waves. The data of TC tracks is from China Meteorological Administration. The historic TCs from 1949 to 2018 were classified into 6 groups according to their tracks, and a representative track is synthesized for each group TCs. We give an extreme strong intensity to the tracks for studying the extreme wave field. The synthesized track of TTC was based on the maximum probability of translation distance and direction of TC center according to historical data. The central pressure (Pc) was used to represent the TC intensity and was studied at 100, 1,000, 10,000 years recurrence period, respectively. The synthetic TC with a representative track and extreme strong intensity is called typical tropical cyclones (TTC). The extreme wave fields driven by TTCs were simulated by SWAN (Simulation Wave Nearshore). The wind field driving waves was calculated by Holland parametric wind model and were well verified with observations. This paper calculated the extreme Hs and Tp of 100, 1,000 and 10,000 years return period for six types of TTC. It was found that the extreme Hs were very different for each TTC. The highest Hs can reach 31.3 m in 10,000 years recurrence period. Followed by TTC-I with 18 m, and TTC-VI is the weakest with less than 10 m. The TC track position frequency and its spatial variation of extreme intensity were discussed. The synthetic tracks have representative and the intensity can be influenced by spatial variation. In the end, four historical typhoons with great intensity, wide impact and serious disaster causing were selected to compare with TTC. This paper can provide a guidance for maritime planners.